2005
DOI: 10.1353/csd.2005.0002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Authorship and Women's Career Decision Making

Abstract: Current career literature provides little insight into how women interpret career-relevant experiences, advice, or information, particularly when it is contradictory. This paper uses findings from interviews with 40 college women to provide empirical confirmation for the link between self-authorship and career decision making. Findings underscore the role of inter-connectivity in women's decision making, particularly involving parents, and distinguish ways that this can reflect self-authorship. Self-authorship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 35 publications
2
69
1
5
Order By: Relevance
“…The fact that many students in the current study said that their expectations for college are largely congruent with those of their parents and that they at least tacitly accept their parents' circumscribed view of acceptable career choices demonstrates that they may not yet have reached the crossroads stage of development. The findings in this study are also consistent with those of Creamer and Laughlin (2005), who studied college women's career decision making and found that many of the women in their sample "turn to parents for advice, if not direction, about career choices" (p. 24). In fact, because these women had not achieved self-authorship and hence defined their own goals in terms of their parents expectations of them, they "are often not in a position developmentally to process information, such as career advice, when it is at odds with Parental Involvement recommendations made by trusted others" (p. 25).…”
Section: Conclusion and Implications For Advising Practicesupporting
confidence: 88%
See 1 more Smart Citation
“…The fact that many students in the current study said that their expectations for college are largely congruent with those of their parents and that they at least tacitly accept their parents' circumscribed view of acceptable career choices demonstrates that they may not yet have reached the crossroads stage of development. The findings in this study are also consistent with those of Creamer and Laughlin (2005), who studied college women's career decision making and found that many of the women in their sample "turn to parents for advice, if not direction, about career choices" (p. 24). In fact, because these women had not achieved self-authorship and hence defined their own goals in terms of their parents expectations of them, they "are often not in a position developmentally to process information, such as career advice, when it is at odds with Parental Involvement recommendations made by trusted others" (p. 25).…”
Section: Conclusion and Implications For Advising Practicesupporting
confidence: 88%
“…While Baxter Magolda does not cite parents as either hindrance or helper in moving their young adult offspring toward selfauthorship, the implication for the current study is that parents as well as faculty members and administrators need to be good company on the journey. Her work has inspired further scholarship showing that parents can be much more influential in women's career choices than experts on campus such as career counselors and faculty members (Creamer & Laughlin, 2005); however, they looked specifically at women's career decisions. Further study that includes men is needed to understand more thoroughly the importance of parents in students' academic and career decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Society's gender-related expectations affect the beliefs concerning future careers of adolescent females more than those of males (Creamer & Laughlin, 2005;Greene & DeBacker, 2004;Plunkett, 2001;Shepard, 2004); in other words, society has a greater influence on the decisions of female adolescents concerning their choice of profession than it does on the decisions of male adolescents. Studies have shown that there are differences between the genders with respect to professional aspirations.…”
Section: To What Extent Do Students Participate In Choosing Their Promentioning
confidence: 99%
“…Teacher characteristics, that is, their ways of knowing and learning, teacher identity and their interpersonal relationships, can be holistically considered using a construct known as self-authorship. Self-authorship is a theory that describes the relationships between critical reflection (evidenced-based evaluations of information) and personal beliefs (Creamer & Laughlin, 2005). As Meszaros (2007) comments, this involves an integrated view of the learner that includes an epistemological dimension (beliefs about the nature of knowledge and knowing), an interpersonal dimension (social relationships) and an intrapersonal dimension (personal values and identity).…”
Section: Cultural-authorshipmentioning
confidence: 99%